Evolutionary economics and regional policy - Jan G. Lambooy; Ron Boschma (European Regional Science Association (ERSA), 1998)
The principal objective of this paper is to formulate some possible links between evolutionary economics and regional policy, a topic that has not (yet) been covered by the literature. We firstly give a brief overview of some issues of regional policy, conceived as a strategy to influence the spatial matrix of economic development. Then, we outline what we take to be the essential arguments and components of evolutionary economics. More in particular, we focus attention on the economic foundation of technology policy from an evolutionary perspective, and how this deviates from the so-called "equilibrium" rationale. Then, we examine in what way evolutionary insights may be helpful for regional policy matters. Our main emphasis is to investigate the degrees fo freedom policy makers may have to determine the future development of regions. When evolutionary mechanisms like chance and increasing returns are mainly involved in the spatial formation of new economic activities, there are several, but quite contradictory, options for policy makers. On the one hand, the importance of early chance events implies that multiple potential outcomes of location are quite thinkable. This is a principal problem for regional policy because new development paths can not be planned or even foreseen. On the other hand, policy makers may have a role to play here. Since space exercises only a minor influence on the location of new economic activities, there is room for policy makers to act and to build-up a favourable local environment. In this respect, urbanisation economies may offer advantages of flexibility secured by a diversity of activities which tends to prevent a process of negative lock-in. When evolutionary mechanisms like selection and path dependency are crucial for the geography of innovation, policy makers are expected to have more influence on the spatial pattern of innovation. In such circumstances, new variety is regarded as strongly embedded in its surrounding environment: the local environment acts as a sort of selection mechanism because it may, or may not, provide conditions favourable to meet the new requirements of new technology. Adaptation to change is largely constrained by the boundaries of the spatial matrix laid down in the past: only minor modifications tend to take place and do not undermine the logic of the spatial system.
Keywords: 330